Model Matematika Pengaruh Pemberian Gadget Terhadap Anak Usia Dini - Nofria Ulfah; Media Rosha (Journal of Mathematics UNP, 2020)
Abstract — Gadgets are sophisticated technology that many people are interested in including early childhood. Parents who deliberately introduce and give gadgets to children without supervision make children addicted to their gadgets. This has led to an increase in cases of gadget addiction in early childhood. The purpose of this research is to form a mathematical model of the effect of giving gadgets to early childhood. This research is basic research. The theoretical method will be used to analyze the theories used in forming a mathematical model of the effect of gadgets on early childhood. Based on the analysis results obtained two fixed points, namely a fixed point free from gadget influence and a fixed point pendemik. The high level of influence of giving gadgets to early childhood causes the population of children to become increasingly addicted to gadgets.Keywords — gadgets, early childhood, gadget addiction.